Sosialisasi Peran Profesi Akuntan untuk Lulusan Akuntansi Pada Era Digital 5.0 - Giovanny Bangun Kristianto; RR Farida Istiningrum; Dianningsih Dianningsih (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
Technological developments in the Digital Era 5.0 have significantly changed the landscape of the accounting profession. Artificial intelligence (AI), big data, blockchain, and the Internet of Things (IoT) are the main factors influencing the transformation in the world of accounting. Accountants are no longer just playing the role of recorders of financial transactions, but are also required to have in-depth data analysis skills and an understanding of new technologies that support efficiency and accuracy in financial management. The biggest challenge faced is the automation of various tasks that were previously done manually, which can reduce the need for conventional accountants. However, on the other hand, this development also opens up opportunities for accountants to increase their role in financial analysis, business planning, and technology-based risk management. This socialization activity aims to provide an understanding to accounting students and high school students regarding the role and challenges of the accounting profession in the digital era. Through a community service program in the form of a Focus Group Discussion (FGD), participants were given insight into the importance of adapting to technological developments and strategies that can be applied to stay relevant in the world of work. The results of this activity showed that the students involved gained a better understanding of the digital transformation in the accounting profession and the importance of developing technology-based skills. Thus, it is expected that future accountants can improve their competitiveness and be ready to face changes in the increasingly digital and complex business world.